Comparison of toughening mechanisms in natural silk-reinforced composites with three epoxy resin matrices. (March 2022) - Yang, Kang; Wu, Zihong; Zhou, Changgeng; Cai, Siyu; Wu, Zhentao; Tian, Wenhan; Wu, Sujun; Ritchie, Robert O.; Guan, Juan
Abstract: Natural silk fibre can reinforce the polymer matrix for composites with improved toughness and impact strength. However, the optimum selection of matrices for the mechanical performance of silk fibre reinforced plastics (SFRPs) is still unclear, especially with respect to toughness. Here Bombyx mori silk is applied to reinforce three epoxy resin matrices with various crosslinking structures. The epoxy resin from bisphenol-A epoxy and aliphatic diamine precursors that is the most ductile and the toughest leads to the SFRPs with the highest tensile breaking energy (14.1 MJ·m −3 ) and impact strength (110 kJ·m −2 ). Examination of the toughening mechanisms in these composites, which haveeither a brittle or ductile matrix, indicated the predominance of crack propagation and fibre pull-out to increase specific energy dissipation during the fracture processes. The rationale for this study is to provide guidelines for the design of matrices in SFRPs with optimal toughness, by identifying the salient toughening mechanisms in these tough and ductile fibre-reinforced composites.